From ratings to action: The impact of ESG performance on corporate innovation - Yan Wang; Xueke Wang (Heliyon, 2024)
This paper aims to investigate the relationship between ESG performance and corporate innovation using a sample of Chinese-listed companies from 2009 to 2021. The findings reveal that ESG performance is positively correlated with both the quantity and quality of corporate innovation. Further, we employed the causal step approach and the Sobel mediation effect test to empirically examine the mechanisms. The results support that ESG performance promotes corporate innovation by reducing agency problems, enhancing information disclosure, and improving internal corporate governance. Heterogeneity analysis indicates that the positive impact of ESG performance on corporate innovation is more pronounced among firms in the central and western regions, as well as those in heavily polluting industries. Notably, we corrected for the truncation-bias in the patent data. This study contributes to the expanding literature on the economic implications of ESG and holds policy implications for promoting the high-quality development of corporate innovation.